Integrating Compulsion Strategy to Improve Students’ English-Speaking Skills Through Podcast - Hasbullah, Hasbullah; Dabamona, Miftahulfadlik; Aulya, Annisa Fitri; Nanning, Nanning (Universitas Negeri Makassar, 2023)
Abstract. This study aims to explore the integration of compulsion strategy and podcasts in improving the students’ English-speaking skills. It’s a teaching challenge in integrating appropriate strategy and media to upgrade students’ English-speaking skills. This study used a mixed-methods to explore the students’ English-speaking skills in integrating the compulsion strategy. A test investigated 42 English students at the Tarbiyah faculty of IAIN Sorong, Indonesia. It tested fluency, vocabulary, pronunciation, and grammar through podcasts. The results showed that most students achieved significant improvement in English-speaking skills after integrating them. The questionnaire was focused on humanism methods: structured planning, regular control, learners’ management, training, the building of interactions, reflection on achievement progress, and re-evaluation of improvement progress. It showed that 86 percent decided strongly agreed and were interested in learning speaking skills utilizing compulsion strategy through podcasts. An interview investigated six respondents whether the compulsion strategy and podcasts could improve students’ English-speaking skills or not. It indicated that most students acquired advantages: enthusiasm to learn English, high self-confidence, and interest in compelled methods using humanism approaches in the teaching process. Therefore, it is recommended to use a compulsion strategy in collaboration with podcast media for teaching and learning English as a foreign language. Keywords: Compulsion Strategy, Podcasts, English-Speaking Skills, Teaching and Learning, Humanism Approaches